Annual Plan 1993-94 Volume-X Hill Areas Government of Assam - Planning Commission (Planning Commission, 1993)
With a view to give more attention to Science education, it has been proposed to create 397 posts of Science teachers one in each of the School during the 8th five year plan. for this purpose it has been proposed to create 200 posts of Science teachers during the current financial year 1992-93. the remaining 197 posts have been proposed to be created during the next four years of the 8th five year plan of which 100 posts has been earmarked during 1993-94.
Government of Assam, Development Commissioner for Hill Areas